Public Policy Implementation: Lessons for the Design. Analysis of Cases of Public Management Modernization and Health Care Reform in Chile - Olavarría Gambi, Mauricio (Revista del CLAD Reforma y Democracia, 2017)
The article analyzes public policy implementation on public management modernization and health care reform occurred in Chile between 1990s and 2010s decades. The analysis is based on the framework provided by Hasenfeld and Brock (1991), whom identify the following main driving forces: the pursuit of rationality, the organization policy-fit, the bureaucratic discretion and adaptation, power relation, and leadership and competence. This work inquires whether those driving forces have been present in the implementation of the analyzed policies and, to do that, it concentrate on the political management of them, the readiness of the basic conditions, factors and necessary circumstances for the operation of the mentioned policies. The document identifies lessons to be considered for the design of public interventions. It concludes that driving forces influencing the public policy implementation process varies in correspondence to the government sector of activity they belong to. Because of that, implementation would not be a process that concrete in the same manner in the different areas of government activity. That implies that public policy design should consider this characteristic of the implementation process and, mainly, in the definition of the characteristics and profile of those who would be in charge of putting in practice the public policy. The unit of analysis is the inter-organizational network in which these public policies have been implemented. Information comes from official documents, press clippings, academic literature and 142 interviews to key actors of these policies.